Democracy chances, here and there - Souza, Eliana Maria de Melo (FCL-UNESP Laboratório Editorial, 2008)
This intervention text synthesizes a dialogue with Yvon Thériault’s work presented in the Lecture ‘Modernism reading matters, Pluralism, Feminism and Political Tolerance’. In this article, there is a return to democracy’s political purpose as a general tolerance social regime, in order to locate it inside the structural parameters of Brazilian political sociability, which are historically based on a deep social inequality.